The justification of the gentiles Paul's letter to the Galatians and Romans - Boers, Hendrikus (Peabody, MA Hendrickson, 1994)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Romans -- criticism, interpretation, etc; Bible. N.T. Galatians -- criticism, interpretation, etc; Justification (Christian theology).